Comparison of Endoscopic Balloon Dilation with Bougie Dilation in Children with Esophageal Atresia - Azizi, Robab; Rohani, Pejman; Hajipour, Mahmoud; Mohajerzadeh, Leily; sadeghi, samane (Iranian Journal of Pediatric Surgery, 2023)
Abstract Introduction: Esophageal stenosis is a complication that can occur following surgical treatment of esophageal atresia. Esophageal stenosis should be treated with some methods. One of these methods is using dilation and there are different devices for dilation. In this study we compared the outcome of the Balloon dilation and Bougie dilation for endoscopic treatment after esophageal atresia. material and methods: this is a cross-sectional study that was performed on 40 pediatrics in two groups including the Bougie group and the Balloon group with equal members. The balloon and bougie dilations were performed for patients and data of these procedures were collected and analyzed. Result: there were 20 pediatrics in both groups and the mean age of all of them was 21/33±12/46 months. All of stenosis symptoms were resolved by performing the bougie or the balloon dilation and these procedures were significantly effective but there was no difference about the balloon dilation or bougie dilation method. Conclusion: there is no difference between balloon and bougie dilation. Both of them can be use for esophageal stenosis